2015
DOI: 10.1002/ajpa.22749
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the human osseous nasal shape—population differences and sexual dimorphism

Abstract: While the bony nose is well suited for predicting population affinity, regarding the populations under investigation, its value for sexing unknown individuals is rather moderate. The similar expression of sexual dimorphism in those otherwise very dissimilar populations indicates common factors responsible for these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 61 publications
3
59
0
Order By: Relevance
“…A few studies of shape in Drosophila found no significant directional asymmetry of wing shape [115][116][117][118][119] or mixed results [120][121][122][123][124][125][126], although a series of other studies did find it [15,16,54,56,62,77,85,123]. Similarly, one study on human skulls [127] found no directional asymmetry of shape, whereas several others reported directional asymmetry of the skull [47,68,84,86,90,94,109] and soft tissues of the face and ears [38,66,98,104,105,108]. Further non-significant results were reported from mites [128] and wings of Trichogramma egg parasitoids [129]-but both studies reported results only from relatively small subsamples (≤30 specimens per sample) and tiny organisms, raising questions about statistical power and possible artifacts from mounting very small specimens.…”
Section: Directional Asymmetrymentioning
confidence: 99%
“…A few studies of shape in Drosophila found no significant directional asymmetry of wing shape [115][116][117][118][119] or mixed results [120][121][122][123][124][125][126], although a series of other studies did find it [15,16,54,56,62,77,85,123]. Similarly, one study on human skulls [127] found no directional asymmetry of shape, whereas several others reported directional asymmetry of the skull [47,68,84,86,90,94,109] and soft tissues of the face and ears [38,66,98,104,105,108]. Further non-significant results were reported from mites [128] and wings of Trichogramma egg parasitoids [129]-but both studies reported results only from relatively small subsamples (≤30 specimens per sample) and tiny organisms, raising questions about statistical power and possible artifacts from mounting very small specimens.…”
Section: Directional Asymmetrymentioning
confidence: 99%
“…Shape asymmetry, involving either matching symmetry or object symmetry [24][25][26] can be estimated from landmarks or semi-landmarks in either two or three dimensions [25][26][27][28][29][30][31][32], as well as continuous symmetry measures [12,[33][34][35]. Despite the apparent simplicity of fluctuating asymmetry, careless researchers can easily reach erroneous conclusions [8,12,22,23,36].…”
Section: Measuring Fluctuating Asymmetrymentioning
confidence: 99%
“…Long bones of the upper limbs, for example, have a right bias in most populations [49][50][51]. Furthermore, parts of the cranial skeleton can also be directionally asymmetric [32,52,53]. One can either remove the directional component [48,54] or decompose a mixture distribution into fluctuating, directional, and antisymmetric components [55].…”
Section: Skeletal Asymmetrymentioning
confidence: 99%
“…To a large degree, this can be attributed to the fact that the majority of studies related to climatic adaption in human nasal morphology have focused on a single morphofunctional unit (Carey & Steegmann, 1981;Cottle, 1955;Crognier, 1981aCrognier, , 1981bDavies, 1932;Franciscus & Long, 1991;Hiernaux & Froment, 1976;Schlager & R€ udell, 2015;Thomson, 1913;Thomson & Buxton, 1923;Weiner, 1954;Woo & Morant, 1934;Yokley, 2009), preventing direct comparisons across different components of the nasorespiratory tract. To a large degree, this can be attributed to the fact that the majority of studies related to climatic adaption in human nasal morphology have focused on a single morphofunctional unit (Carey & Steegmann, 1981;Cottle, 1955;Crognier, 1981aCrognier, , 1981bDavies, 1932;Franciscus & Long, 1991;Hiernaux & Froment, 1976;Schlager & R€ udell, 2015;Thomson, 1913;Thomson & Buxton, 1923;Weiner, 1954;Woo & Morant, 1934;Yokley, 2009), preventing direct comparisons across different components of the nasorespiratory tract.…”
mentioning
confidence: 99%
“…While these previously discussed studies have provided important insights into ecogeographic variation in human internal nasal fossa morphology, it still remains unclear whether the internal nasal fossa actually exhibits stronger associations with climate compared to the external pyramid, nasal aperture or nasopharynx. To a large degree, this can be attributed to the fact that the majority of studies related to climatic adaption in human nasal morphology have focused on a single morphofunctional unit (Carey & Steegmann, 1981;Cottle, 1955;Crognier, 1981aCrognier, , 1981bDavies, 1932;Franciscus & Long, 1991;Hiernaux & Froment, 1976;Schlager & R€ udell, 2015;Thomson, 1913;Thomson & Buxton, 1923;Weiner, 1954;Woo & Morant, 1934;Yokley, 2009), preventing direct comparisons across different components of the nasorespiratory tract. Further, the few studies (Charles, 1930;Evteev et al, 2014;Fukase et al, 2016;Franciscus, 1995;Noback et al, 2011) incorporating multiple morphofunctional units have either assessed climatic associations across all the units collectively, preventing assessment of each unit's independent association with climate (Noback et al, 2011), or have employed samples which do not encompass the full range of climates encountered by modern humans (Charles, 1930;Evteev et al, 2014;Franciscus, 1995;Fukase et al, 2016).…”
mentioning
confidence: 99%